Bacterial pathogens in the non-clinical environment - Sebastien P Faucher (Frontiers Research Topics, 2015)
The transmission route used by many bacterial pathogens of clinical importance includes a step outside the host; thereafter refer to as the non-clinical environment (NCE). Obvious examples include foodborne and waterborne pathogens and also pathogens that are transmitted by hands or aerosols. In the NCE, pathogens have to cope with the presence of toxic compounds, sub-optimal temperature, starvation, presence of competitors and predators. Adaptation of bacterial pathogens to such stresses affects their interaction with the host. This Research Topic presents important concept to understand the life of bacterial pathogens in the NCE and provides the reader with an overview of the strategies used by bacterial pathogens to survive and replicate outside the host.